Testing the Fisher hypothesis in the presence of structural breaks and adaptive inflationary expectations: Evidence from Nigeria - Stephen O. U. Uyaebo; Yakubu A. Bello; Babatunde S. Omotosho; Suleiman Karu; Satumari A. Stephen; Raymond O. Ogbuka; Balarabe F. Usman; Oluwaseun D. Mimiko (CBN Journal of Applied Statistics, 2016)
This paper tested for the validity of the Fisher hypothesis in Nigeria during the period 1970 - 2014. The Gregory and Hansen Co-integration test confirmed the existence of a long-run relationship between nominal interest rates and inflation, albeit with a structural break in October 2005. In addition, the obtained Fisher coefficient in the cointegrating relation was 0.08, implying a weak form of Fisher effect in the long-run. On the basis of these findings, we upheld a weak Fisher effect in the long-run and non-existence of Fisher effect in the short-run. This implied that short term nominal interest rate is a good characterization of monetary policy stance. Also, the obtained partial Fisher effect indicated that changes in monetary policy are capable of altering the long term real interest rate and influencing economic growth through the interest rate channel. We therefore recommend a more forward looking monetary policy as a way of anchoring inflationary expectations and ensuring low and stable prices in Nigeria.
Keywords: C32; E43; E44; 330; Fisher effect; Structural change; Co-integration; Breakpoints regression; Interest rates